2022
DOI: 10.1002/ece3.8797
|View full text |Cite
|
Sign up to set email alerts
|

Analytical approaches for evaluating passive acoustic monitoring data: A case study of avian vocalizations

Abstract: 1. The interface between field biology and technology is energizing the collection of vast quantities of environmental data. Passive acoustic monitoring, the use of unattended recording devices to capture environmental sound, is an example where technological advances have facilitated an influx of data that routinely exceeds the capacity for analysis. Computational advances, particularly the integration of machine learning approaches, will support data extraction efforts. However, the analysis and interpretati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 114 publications
(160 reference statements)
1
7
0
Order By: Relevance
“…The aim of our study, therefore, is to analyze richness and compositional differences between acoustic subsetting scenarios across three choice gradients, revealing the potentially missed detection opportunities and across biologically relevant time periods. We not only replicate previous research for a central European forest context for how effort allocation scenarios (hereafter scenarios) affect species richness (Cook & Hartley, 2018 ; de Araújo et al, 2021 ; La & Nudds, 2016 ; Symes et al, 2022 ; Wimmer et al, 2013 ; Wood et al, 2021 ) but we also additionally analyze how these scenarios affect revealed assemblage composition. To do this we considered three main parameters of acoustic file selection: (1) recording intensity, i.e., number of minutes within 1 h; (2) day phase, i.e., period of the morning in relation to sunrise (dawn, morning, or both); and (3) duration, i.e., number of days included in the subset.…”
Section: Introductionsupporting
confidence: 60%
See 4 more Smart Citations
“…The aim of our study, therefore, is to analyze richness and compositional differences between acoustic subsetting scenarios across three choice gradients, revealing the potentially missed detection opportunities and across biologically relevant time periods. We not only replicate previous research for a central European forest context for how effort allocation scenarios (hereafter scenarios) affect species richness (Cook & Hartley, 2018 ; de Araújo et al, 2021 ; La & Nudds, 2016 ; Symes et al, 2022 ; Wimmer et al, 2013 ; Wood et al, 2021 ) but we also additionally analyze how these scenarios affect revealed assemblage composition. To do this we considered three main parameters of acoustic file selection: (1) recording intensity, i.e., number of minutes within 1 h; (2) day phase, i.e., period of the morning in relation to sunrise (dawn, morning, or both); and (3) duration, i.e., number of days included in the subset.…”
Section: Introductionsupporting
confidence: 60%
“…To our knowledge, no studies exist that also directly address how perceived bird species composition is affected by acoustic file selection choices, but such investigations are recommended (Symes et al, 2022). Wood et al (2021) addressed species composition insofar as they used simulated bird assemblages to investigate how assemblage structure affects richness estimates depending on how many theoretically rare species comprise the assemblage.…”
Section: T a X O N O M Y C L A S S I F I C A T I O Nmentioning
confidence: 99%
See 3 more Smart Citations